Annular elastolytic giant cell granuloma: A report of 10 cases - Sandeep Arora; Ajay Malik; Chetan Patil; Anil Balki (Wolters Kluwer Medknow Publications, 2015)
Annular elastolytic giant cell granuloma initially described by O'Brien in 1975 is a disorder of uncertain etiopathogenesis presenting with annular erythematous plaques predominantly on the sun-exposed areas. Hisptopathologically, it is characterized by elastin degenration, multinucleate giant cells, and elastophagocytosis. The authors came across 10 such cases, which were managed with hydroxychloroquine resulting in complete resolution in 4-6 months.